Children at both ends of the gun : towards a comprehensive legal approach to the problem of child soldiers in Africa - Sloth-Nielsen, Julia (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.